New Asian Hydroscapha, with comments on male-female association of co-occuring species (Coleoptera, Myxophaga, Hydroscaphidae) - Fikáček, Martin; Šípková, Hana (Zootaxa, 2009)
Four syntopically co-occuring species of the genus Hydroscapha LeConte, 1874 are recorded at three adjacent hygropetric localities in the Indian state of Meghalaya (Khasi Hills). Association of males with conspecific females was recognized as a crucial problem for the taxonomic treatment of these taxa. Antennal morphology and abundance data of all collected morphotypes and their presence/absence at each locality were used for this association; most of these data are, however, shown as insufficient for a reliable association due to intraspecific variability (in the case of antennal morphology) or incomplete knowledge of seasonal dynamics (in the case of relative abundance of males versus females). Utilizing male characters separately from those of females is suggested as a possible solution. Following this approach, updated identification keys for males and females of Asian Hydroscapha and tables summarizing useful diagnostic characters are provided. Disadvantages of this approach are also discussed. The examined samples include two species described as new (Hydroscapha khasiorum sp.n. and H. rajani sp.n.) and H. monticola Löbl, 1994, which is recorded in India for the first time. A fourth species currently represented by one specimen only is left unidentified.